Cardiologist and Diabetologist crosstalk in the era of cardiovascular outcome trials of novel glucose-lowering drugs. (December 2018) - Maranta, Francesco; Cianfanelli, Lorenzo; Regoni, Maria; Cianflone, Domenico
Abstract: The prevalence of type 2 diabetes continues to increase and cardiovascular (CV) diseases remain the leading cause of death in diabetic patients. Diabetologists and Cardiologists have to work together in order to provide the best management to these patients. After years of disappointing studies showing no reduction of CV events with strict glycaemic control, some of the novel glucose-lowering drugs (GLDs) seem to offer a new approach to tackle the problem, since the CV outcome trials (CVOTs-D) of liraglutide, semaglutide, empagliflozin and canagliflozin have demonstrated not only their CV safety but also their efficacy in the reduction of CV morbidity and mortality. Along with the initial enthusiasm, concerns have been raised about the economical sustainability of long-term therapies considering higher costs of new molecules relative to the traditional ones. As expenses in the medical field are on the rise, healthcare systems need to balance the positive impact of an intervention and its overall cost. This review is meant to offer the Cardiologists a different point of view on the positive influence of GLDs, in the light of the main trials in the CV fields they are familiar with. The purpose of this article is to critically review the magnitude of the CVOTs-D results by the analysis of their statistical determinants, to establish the extent of the GLDs positive impact on patients with both diabetes and CV disease. The analysis has been performed taking into account models and statistical determinants used in the main landmark cardiology trials. It is fundamental to translate the result of CVOTs-D in clinical practice: the interdisciplinary crosstalk between the Cardiologist and Diabetologist is of paramount importance in order to fully exploit the power of the new available pharmacological strategies.